La politique extérieure du Chili : le retour aux origines - Juan Gabriel Valdés (Cahiers des Amériques Latines)
This article offers an analysis of Chile’s foreign policy since the return of democracy in the early 1990s, highlighting the two main guidelines that characterize it, regardless of changes in government: firstly, the necessity of increasing trade agreements in the context of globalisation, and secondly, the necessity of deepening dialogue on regional integration while adhering to its traditional principles of respect for treaties and international law. However, by successively examining relations with Argentina, Bolivia and Peru, the author reports the modernising and multilateral ambition of Chilean foreign policy in the last two decades, together with the permanence of ancient legacies in a number of bilateral relations.